The Effect of Liner Composition of Artificial Vagina on The Survival of Bovine Spermatozoa - Salhab, S. A; Merilan, C. P. (Al-Mukhtar Journal of Sciences, 2026)
The Effect of liner-collection cone (One Piece) composition upon survival of bovine spermatozoa was studied in this paper. 40 ejaculates of semen were collected from mature Holstein - bulls using polyethylene or rubber liners collection cones (One-Piese , 69 cm). Each ejaculate was extended in sodium citrate buffer extender containing 15% egg - Yolk. Glycerol solution was added in four steps to give a final glyceral concentration of 8% . The extended semen samples were then equilibrated at 5°C for 2 h, packaged in 0.5 ml French straws and frozen by suspending the straws 5 cm above liquid nitrogen. Frozen samples were stored for 24 hs in liquid nitrogen and thawed at 41° C. for 15 seconds. Analysis of variance findings for progressive motility and unstained bovine spermatozoa show highly significant differences (P